The effect of trimetazidine on intrahepatic cholestasis caused by carmustine in rats - Demir, A; Özütemiz, Ö; Yildiz, C; Yüce, G; Tekesin, O; Ilter, T (Wiley, 2001)
This study investigated the effect of trimetazidine (TMZ), known as an anti-oxidant agent, on intrahepatic cholestasis caused by Carmustine (BCNU) in rats. Rats were assigned into four groups. The first group (Saline) consisted of 12 rats, which were injected with 2 ml/kg of saline intraperitoneally (IP) 48 h before the study. The second group (corn oil group, n = 15), which were injected with 2 ml/kg of corn oil IP 48 h before the study. The third group (BCNU group, n = 16), which were injected with 2 ml/kg of corn oil + 25 mg/kg BCNU IP 48 h before the study. The fourth group (TMZ group, n = 12), which were injected with 2.5 mg/kg per day of TMZ IF, administered at the same hour of the day as a single-dose. Twelve hour after the first dose of TMZ, corn oil 2 ml/kg + BCNU 25 mg/kg IP were injected, and the rats were included in the study 48 h after the administration of corn oil + BCNU. Following a pentobarbital anaesthesia, abdomen was opened with incision, a cannula was placed into the channel of choledocus, and the amount of bile was measured per hour. Then intracardiac blood sample was taken, and consequently centrifuged to obtain the plasma. Finally, the rats were killed with cervical dislocation, and their livers were removed and weighted. In addition to histopathological examination of liver, the levels of malon dialdehyde (MDA), oxidised glutation (GSSG), and reduced glutation (GSH) were detected. Also the osmolality of bile and plasma was estimated in mOsm/kg. As a result, the biliary flow was seen to decrease in BCNU group (P < 0.005), but to be normal in TMZ group. The serum level of conjugated biluribin was higher in BCNU group compared to other groups (P < 0.05 for each). Although the level of total glutation was lower (P < 0.005) in TMZ group, GSH/GSSG ratio was normal. These findings suggest that TMZ has a protective effect on intrahepatic cholestasis caused by BCNU. <(c)> 2001 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: carmustine; trimetazidine; intrahepatic cholestasis